New records of Lumbrineridae (Annelida: Polychaeta) in the Mediterranean biogeographic province, with an updated taxonomic key. Issue 2 (2nd April 2016) - D'Alessandro, M.; Romeo, T.; Castriota, L.; Cosentino, A.; Perzia, P.; Martins, R.
Abstract: The present study is a part of a larger project aiming to characterise the benthic macrofaunal assemblages from the Gulf of Milazzo (Southern Tyrrhenian Sea, Central Mediterranean). Forty-eight samples from 16 sites were collected during the summer of 2010 by means of van Veen grab (0.1 m 2 ) at 20 and 50 m depths to characterise taxonomically, ecologically and biogeographically the present species of Lumbrineridae. Sandy-silt mixed sediments characterised the study area. Abyssoninoe hibernica and Lumbrineris luciliae are newly recorded for the Mediterranean Sea, and Gallardoneris iberica, Lumbrineris geldiayi and Lumbrineris lusitanica are new records for the Central Mediterranean Sea. Therefore, a total of 29 species of Lumbrineridae are currently present and recognised on Mediterranean coasts. Additionally, we provide an updated key to the Mediterranean species of the family.